Perbedaan Frekuensi Konsumsi Fast Food dan Asupan Lemak dengan Kejadian Menarche pada Remaja Putri di SMP Muhammadiyah 1 Surakarta - Sariyana, Dini Gati; , Elida Soviana, S.Gz., M.Gizi; , Susi Dyah Puspowati, S.P., M.Si (2016)
Introduction: Menarche is the first hemorrhage from uterine which happens in female adolescents. Menarche is related to several factors such as genetics, nutritional status, socio-economic, frequency of fast food consumption, high fat food consumptions and exposure to adult content media. Objective: The aims of this study were to determine differences in the frequency of fast food consumption and fat intake between early and normal menarche aldolescents at Muhammadiyah 1 Junior High School of Surakarta. Method : This research was an observational research with cross-sectional approach. Number of subject was 80 students which were recruited using simple random sampling method. The data collection on fast food consumption and fat intake were obtained using Semi-quantitative Food Frequency Questionnaire. Statistical analysis used Mann Whitney and Independent t-tests. Result : Research showed that frequency of fast food consumption most of adolescents at the rare category (80% in early menarche and 82,5% normal menarche). Most adolescents had a good fat intake (67,5% in early menarche and 60% normal menarche). The results of comparison tests showed p value= 0.745) in frequency of fast food consumption and p value= 0.789 in fat intake between early and normal menarche adolescents. Conclusion : There were no differences in the frequency of fast food consumption and fat intake between early and normal menarche adolescents at Muhammadiyah 1 Junior High School of Surakarta. Key Word : frequency of fast food consumption, fat intake, adolescents, menarche.